Workshop for the Standardization of concepts of Information Sciences - Harper Alvarado, Marlene (1983)
Bibliotecología's Unit, as contribution to the normalization of concepts on the Information in the ONE, carries out the days for the normalization of the concepts of Sciences of the Information and consolidation of the information system for the Faculty of Philosophy and Letters.